Educação e diversidade de gênero: experiências escolares de travestis em São Luís-Ma - RIBEIRO, Ruy Tadeu Costa (2020)
We give the understanding of gender identity as subjective identifications which we comprehend as male and female characteristics or as side effects of social deconstructions about biological sex be the indicator of individuals’ identities, behaviors, personal likes and sexual desires. Be against of biological perceptions, in most time, results in the comprehension of escape from social normality, having exclusions as answers to attempts to exercise the right to exist. Among excluding means, we highlight schools environments that owns the speech of being the center of diversities meeting but become restricted when they are against discussions about gender diversity like thinking about an included education for travestis. Since its beginning, the school performed a function in service of thoughts modes and discrimination standardization about people by mechanisms of ordination, hierarchization and classification. This study was searching, therefore, understand how is the relationship between education and gender diversities from travestis’ school experiences and the repercussions in their subjectivationprocess. The goal of this study is achieve analysis about travestis’ school experiences bringing questions about the relationship between education and gender diversities, consequently, discussing the history of the relationship between education and gender diversity in Brazilian society correlating travestis school experiences and their repercussions in the process of subjectivation and thinking about perspectives of an education that can understand gender diversity from travestis speech. For this, was developed a study classified as action research, with qualitative approach, interviewing three travestis who experienced the educational system in São Luis, regardless of school level (basic education, high school or higher education) by a semi-structured interview, faithfully recorded and transcribed, taking inspiration from Foucault’s concepts about speech analysis to execute data analysis. Then, was noticed that excluding experiences, able to interfere in subjective construction of their identities and social coexistation, that can restrict future perspectives and labor opportunities, are marked in people that confront biological norms of gender in school. However, even it was an aversive environment, they valorize the importance of formal education, proposing an urgent need to school system in order to guarantee for all people the right of access and stay, against all ways of discrimination and standardization of individuals’ expressions. Finally, this study goes beyond the school experiences, showing itself as motivation to develop new studies and to increase the study about several discussions.